An Overview of Linear Structural Models in Errors in Variables Regression - Jonathan Gillard (Revstat, 2010)
This paper aims to overview the numerous approaches that have been developed to estimate the parameters of the linear structural model. The linear structural model is an example of an errors in variables model, or measurement error model that has wide practical use. This paper brings together key concepts from a scattered literature to give an accessible account of existing work on this particular errors in variables model.